THE EFFECTS OF BRAND ENDORSEMENT, POPULARITY, AND EVENT SPONSORSHIP ON CONSUMER PRE-PURCHASE ATTITUDES IN JAKARTA - Daniel Hendrasaputra; Andy Lunarjanto (Bina Nusantara University, 2009)
It aims to investigate the individual and collective effects of Brand Endorsement, Popularity, and Event Sponsorship on consumer perceived quality, uniqueness, manufacturer esteem, and corporate citizenship. This research uses Frequency Analysis, Descriptive Analysis (Mean and Standard deviation), Independent Samples T-Test, ANOVA and MANOVA It suggest significant main effects for both popularity and sponsorship cues, with popularity affecting perceived quality, uniqueness, and manufacturer esteem, and sponsorship affecting manufacturer esteem and corporate citizenship Popularity is the most managerially useful, because it can give significant effects on perceived product quality, uniqueness, and manufacturer esteem. Sponsorship can give significant effects on corporate image, represented in manufacturer esteem and corporate citizenship.